The Effectiveness of Write-Pair-Square and Group Investigation to Teach Writing Descriptive Text for Students With High and Low Participation - Faticha, Dewi; Anggani Linggar Bharati, Dwi; Warsono, Warsono (English Education Journal, 2019)
Recently, teaching and learning English as foreign language has raised its position as a trending field in language transformation in Indonesia.This study aimed to measuring the effectiveness of Write-Pair-Square and Group investigation to teach writing descriptive text as two cooperative learning strategies. There were 50 students of the seventh grade students of MTs N Tegal. This study used an experimental method with pre-test and post-test of a 2x2 factorial design. Two classes were chosen as experimental group 1 and 2, while the third class was chosen for tryout. The data of students’ participation level was gained from observation before the treatments and the data of students’ writing achievement was gained from writing test. The data from the test was analyzed with T-Test and ANOVA Test. The results revealed that there was significant difference of the students’ participation on the post-test result after being taught by using Write-Pair-Square and Group Investigation strategies. Then, the result of the significance value (p value) of teaching strategies and participation was 0.032 < 0.05. Thus, it can be stated that there is effective interaction among strategies and participation to enhance students’ writing achievement.